OUTCOME OF SHORT AND LONG DURATION STEROID THERAPY IN CHILDHOOD NEPHROTIC SYNDROME IN TERMS OF FREQUENCY OF RELAPSE RATE - Abdul Ahad Jamshaid; Akhtar, Naureen; Adnan, Aneeqa; Perveen, Shahida; Chaudhry , Adeela; Tatima, Tehreem (Journal of Ayub Medical College Abbottabad, 2022)
Background: Nephrotic syndrome is a clinical syndrome defined by massive proteinuria (greater than 40 mg/m2/hour) responsible for hypoalbuminemia (less than 30 g/L) resulting in oedema and hyperlipidaemia. Objective of the study was to compare the frequency of relapse rate with short and long duration steroid therapy in Nephrotic syndrome. It was a Quasi-experimental control group design, conducted at the Department of Paediatric Nephrology, The Children’s Hospital and Institute of Child Health, Lahore. Duration of study: One year. Method: The data of 150 patients with steroid sensitive nephrotic syndrome was included with clinical presentation and diagnostic investigations. The children were randomly divided into long and short duration steroid treatment groups. Outcome was determined in terms of relapse rate after achieving remission with both treatment strategies. Independent sample t test was applied to compare the outcome in both groups with p‰¤0.05 considered as significant. Data was stratified for all the effect modifiers like age and gender and post-stratification chi square test was applied to see the effect on the outcome, taking p‰¤0.05 as significant. Results: The relapse rate of the disease was 0.8±0.72 per year in short-duration group and 1.28±0.61 per year in subjects receiving long-duration steroids, and difference between the two groups was found to be statistically significant (p<0.001). The relapse rate was less in the short duration therapy group as compared to the long duration therapy 62.7% (n=47) patients in group A had one or more relapses of the disease within one year of follow up in contrast to 94.7% (n=71) children in group B (p<0.001). Conclusion: Patients receiving short duration steroid therapy showed a lower relapse rate as compared to those who were administered long term steroids.